4β‐hydroxycholesterol correlates with dose but not steady‐state concentration of carbamazepine: indication of intestinal CYP3A in biomarker formation? - Gjestad, Caroline (Br J Clin Pharmacol, 2015)
AIM: 4β‐hydroxycholesterol (4βOHC) is an endogenous CYP3A(4) biomarker, which is elevated by use of the CYP3A4 inducer carbamazepine. Our aim was to compare to what extent serum concentration of 4βOHC correlates with dose (presystemic exposure) and steady‐state concentration (systemic exposure) of carbamazepine. METHODS: The study was based on a therapeutic drug monitoring material, including information about daily doses and steady‐state concentrations (C (ss)) of carbamazepine. 4βOHC concentrations were determined in residual serum samples of 55 randomly selected carbamazepine‐treated patients and 54 levetiracetam‐treated patients (negative controls) by UPLC‐APCI‐MS/MS after liquid–liquid extraction. Correlation analyses between 4βOHC concentration and daily dose and C (ss) of carbamazepine, respectively, were performed by Spearman's tests. In addition, 4βOHC concentrations in females vs. males were compared in induced and non‐induced patients. RESULTS: Median 4βOHC concentration was ~10‐fold higher in carbamazepine‐ vs. levetiracetam‐treated patients (650 vs. 54 nmol l(−1), P < 0.0001). There was a significant, positive correlation between carbamazepine dose and 4βOHC concentration (Spearman r = 0.53, 95% confidence interval [CI] 0.27, 0.72, P < 0.001). No significant correlation between carbamazepine C (ss) and 4βOHC concentration was found (Spearman r = 0.14; 95% CI −0.14, 0.40, P = 0.3). Enzyme‐induced females had significantly higher 4βOHC concentrations than males (P < 0.001), while no significant gender difference was found in non‐induced patients (P = 0.52). CONCLUSION: Serum concentrations of 4βOHC correlate with presystemic, but not systemic exposure of the CYP3A4 inducer carbamazepine. This suggests a stronger inductive effect of carbamazepine on presystemic than systemic CYP3A4 phenotype and might indicate a role of the intestine in 4βOHC formation. Moreover, CYP3A4 inducibility seems to be higher in females than males.